Association of major dietary patterns with socioeconomic status, obesity, and contracting COVID-19 among Iranian adults - Maharat, Maryam; Rahimlou, Mehran; Sioofi, Ali; Sajjadi, Seyedeh Forough; Moosavian, Seyedeh Parisa (Frontiers in Nutrition, 2024)
The coronavirus disease 2019 (COVID-19) pandemic clearly affected lifestyle and dietary habits of millions of people worldwide. The purpose of this study was to evaluate the association of major dietary patterns with socioeconomic status, obesity and contracting COVID-19.We conducted a cross-sectional study using an online survey for data collection with a total of 1187 participants (over the age of 18 years old) reported their sociodemographic details, anthropometric index (weight and height), and dietary intake. Multivariable logistic regression models was applied to assess the association between major dietary patterns and study outcomes.Results: A total of 1106 adults were included in the current analysis. We identified three major dietary patterns (plant based, meat, and western dietary patterns). The mean age of participants was significantly higher in the upper tertile of plant based dietary patterns (DP) compared to the first tertile, while it was lower in the top tertile of meat and western DP. The percentage of participants lived in urban was significantly higher in third tertile of meat DP than first tertile (P<0.001). The moderate adherence to western DP was significantly associated with increased odds of obesity (OR: 1.79; 95% CI: 1.17, 2.74). Also, high adherence to western DP was significantly related with increased odds of obesity, after controlling for confounders. Subjects in the second tertile of the western DP had higher odds (95% Cl: 1.04, 1.92) for COVID-19 infection compared to the first tertile.This study showed that moderate and high adherence to a western dietary pattern were associated with higher risk of obesity, and COVID-19 infection during the pandemic.Future studies are needed to confirm these findings.